Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(85.\left(x+2\right)=170\)
\(\Rightarrow85x+170=170\)
\(\Rightarrow85x=0\)
\(\Rightarrow x=0\)
\(\frac{75.5^4+175.5^4}{20.25.125-625.75}=\frac{\left(75+175\right).5^4}{4.5.25.5^3-5^4.75}\)
\(=\frac{250.5^4}{100.5^4-5^4.75}=\frac{250.5^4}{\left(100-75\right).5^4}\)
\(=\frac{250}{25}=10\)
72 : ( x - 15 ) = 8
x - 15 = 72 : 8
x - 15 = 9
x = 9 + 15
x = 24
Vậy x = 24 .
Học tốt !
Ta có: \(3n+1⋮n-1\)
\(\Rightarrow3\left(n-1\right)+4⋮n-1\)
\(\Rightarrow4⋮n-1\)(vì \(3\left(n-1\right)⋮n-1\))
\(\Rightarrow n-1\in\left\{-4;-2;-1;1;2;4\right\}\)
\(\Rightarrow n\in\left\{-3;-1;0;2;3;5\right\}\)
Hok "tuốt" nha^^
( 3x + 1 )\(^3\)= 64
( 3x + 1 )\(^3\)= 4\(^3\)
=> 3x + 1 = 4
3x = 4 - 1
x = 3 : 3
x = 1
Vậy, x = 1
x.x+3x=18
\(\Rightarrow\)x.(x+3)=18
Mà 18=3.6=3.(3+3)
nên x=3
x*x+3x=18
=>x2+3x-18=0
=>x2+6x-3x-18=0
=>x(x+6)-3(x+6)=0
=>(x-3)(x+6)=0
=>x-3=0 hoặc x+6=0
=>x=3 hoặc x=-6
Ta có: (x-1)\(^{11}\)=(x-1)\(^{13}\)
\(\Leftrightarrow\)(x-1)\(^{11}\)-(x-1)\(^{13}\)=0
\(\Leftrightarrow\)(x-1)\(^{11}\).[1-(x-1)\(^2\)]=0
\(\Leftrightarrow\orbr{\begin{cases}\left(x-1\right)^{11}=0\\1-\left(x-1\right)^2=0\end{cases}}\)\(\Leftrightarrow\)\(\orbr{\begin{cases}x-1=0\\\left(x-1\right)^2=-1hoặc\left(x-1\right)^2=1\end{cases}}\)\(\Leftrightarrow\orbr{\begin{cases}x=1\\x=0hoặcx=2\end{cases}}\)
Vậy x=1, x=0 hoặc x=2
6 nha
@@@
@@@@
HT